Optimization of the lubricating oil inventory policy applied in a mining company. Issue 6 (3rd July 2021) - Senses, Sena; Golbasi, Onur; S. Bakal, Ismail
ABSTRACT: The mining industry should sustain mass and continuous production with an essential contribution of high-capacity machinery. Therefore, spare parts inventory management is vital in ensuring the intended mining production rate as an integral part of maintenance policies. In this paper, a mixed-integer model is presented to solve a multi-item and multi-supplier spare parts inventory model. This model is addressed to a lubricating oil inventory problem in one of the biggest multi-process mining companies in Turkey. The optimisation results show that the company's current lubricating oil inventory policy can be improved financially by yielding an annual saving up to ₺18, 566.